Organic farming: offering women entrepreneurs access to high-value niche markets - Bafana, Busani; Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2019)
Organic agriculture in ACP regions is improving the livelihoods of women farmers, who are selling high value products to global niche markets. Two examples, from Jamaica and Samoa, illustrate the scope for organic agriculture to empower women agripreneurs